Squat Movement Analysis of Futsal Players with Leg Injury History: A Biomechanics Review (Universitas Pendidikan Indonesia, 2025)
The aim of this study was to analyze squat movements of futsal players who have leg injury history. The research method used in this study was descriptive analytics with a one-shot case study design. The samples were given one treatment and then were observed to obtain the results of the treatment. This study involved 9 Kapten Muda Futsal Academy futsal players who had a history of leg injuries as samples selected using purposive sampling technique. The results showed the mean of spinal tilt angle 65.56 ± 6.19 degrees, hip angle 80.44 ± 6.64 degrees, knee angle 67.52 ± 10.35 degrees, and ankle angle 54.66 ± 6.50 degrees. It concludes that squats performed by Kapten Muda Futsal Academy futsal players who had leg injury history were not optimal and had not been able to reach the 90 degree squat position. This study found that poor ankle mobility, an angle less than 35 degrees, and the history of knee injury will get a squat with a body tilt position leaning forward and backward, causing the squat movement to be not optimal. The optimal squat technique should have feet shoulder width apart and knee movement no further forward than the toes, gaze in a forward position, and do the squat position at full depth 115-125 degrees. However, this study only used one camera to record squat movements to analyze hip, spine, knee, and ankle angles. It is hoped that future studies analyze the squat movement at a full depth position of 125 degrees.